(untitled) (Journal of Atomic and Molecular Sciences, 2019)
Hydrogen evolution reaction (HER) is long considered as a promising chemical reaction that can produce the clean fuel hydrogen to resolve the energy crisis and environmental pollution. Herein, we report the in situ growth of Co-Ni-Se network on a 3D porous Ni foam support (Co-Ni-Se/NF) as an efficient electrocatalyst for HER. The obtained Co-Ni-Se/NF electrode exhibits high HER activity that only needs a low overpotential of 106 mV at 10 mA cm^-2.